Contraceptive efficacy and safety of estradiol valerate/dienogest in a healthy female population: a multicenter, open-label, uncontrolled Phase III study - Yu Q; Huang ZR; Ren ML; Chang Q; Zhang Z; Parke S (Dove Medical Press, 2018)
Qi Yu,1 Zirong R Huang,2 Mulan Ren,3 Qing Chang,4 Zhongqi Zhang,5 Susanne Parke61Department of Obstetrics and Gynecology, Peking Union Medical College Hospital, Beijing, China; 2Department of Family Planning, Obstetrics & Gynecology Hospital of Fudan University, Shanghai, China; 3Department of Obstetrics and Gynecology, Zhongda Hospital, Southeast University, Nanjing, China; 4Department of Obstetrics and Gynecology, Southwest Hospital, Third Military Medical University, Chongqing, China; 5Bayer Healthcare Co., Ltd., Beijing, China; 6Bayer Pharmaceuticals, AG, Berlin, Germany Background: To investigate the efficacy and safety of a combined oral contraceptive containing estradiol valerate and dienogest (EV/DNG) in healthy Asian women.Methods: In this multicenter Phase III study, women received oral EV/DNG in a 28-day regimen for 13 cycles. The primary efficacy endpoint was the number of unintended pregnancies, measured by the Pearl Index (PI); secondary efficacy endpoints included bleeding pattern and cycle control parameters. Adverse events were monitored during the study and overall satisfaction with treatment was determined on completion of the study.Results: A total of 954 Asian women (97.7% of subjects assigned to study medication; mean age 33.4 years) were treated. Five pregnancies were reported during EV/DNG treatment over 796.34 relevant woman-years of exposure, giving an unadjusted PI of 0.63 and a cumulative failure rate of 0.0049; 3 pregnancies during EV/DNG treatment over 760.35 relevant woman-years of exposure gave an adjusted PI of 0.39. The bleeding pattern improved during the reporting periods within the study. The proportion of women who experienced withdrawal bleeding decreased with treatment (84.9% of women during Cycle 1 vs 79.3% in Cycle 13), and the mean length of withdrawal bleeding decreased with treatment (4.2 vs 3.4 days). The number and maximum length of intracyclic bleeding/spotting episodes also decreased with EV/DNG. EV/DNG was well tolerated, and 92% of women included in the study were very satisfied or somewhat satisfied with EV/DNG.Conclusion: EV/DNG showed high contraceptive efficacy, was well tolerated in Asian women, and may be effectively used in this population.Clinical trials registry: ClinicalTrial.gov identifier: NCT01638910.Keywords: Asian, bleeding pattern, combined oral contraceptive, cycle control, estradiol valerate/dienogest, women